THE CONTRIBUTION OF SOCIAL ATTITUDES, LEARNING INTEREST, ANDTEACHER COMPETENCE TOWARD THE FIFTH-GRADE ELEMENTARY STUDENTS’ADAPTIVE SKILLS IN SEMESTER II AT CLUSTER 3 TABANAN - Gusti Ayu Sri Mahartini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The contribution of social attitudes, interest in learning, and teacher competence toward the fifth-grade elementary students’ adaptive skills in semester II at cluster 3 is discussed in this paper. The research is ex-post-facto research. The population is 137 students. The data collection method is a questionnaire. Based on the research that has been conducted, it is concluded that 1) there is a contribution of social attitudes toward the fifth-grade elementary students’ adaptive skills in Semester II at cluster 3 in Tabanan with a contribution of 23.50% and an effective contribution of 8.52%. Hereafter, 2) there is a contribution of learning interest toward the fifth-grade elementary students’ adaptive skills in Semester II Cluster 3 in Tabanan with a contribution of 32.9% and an effective contribution of 15.60%. In addition, 3) there is a contribution of teacher competence toward the fifth-grade elementary students’ adaptive skills in semester II at Cluster 3 in Tabanan with a contribution of 37.50% and an effective contribution of 24.97%. Lastly, 4) there is a significant contribution of social attitudes, learning interest, and teacher competence simultaneously toward the fifth-grade elementary students’ adaptive skills with a contribution of 49.10%.